Sexuality and the Culture of Silence in Colm Tóibín’s “The Pearl Fishers” - Carregal Romero, José (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2015)
Colm Tóibín’s narrator in “The Pearl Fishers” (The Empty Family, 2010) is a middle-aged homosexual man who shares dinner with two friends from school, Gráinne and Donnacha, a married couple and faithful representatives of the Irish laity. To the narrator’s surprise, Gráinne announces her intention to publish a book detailing her sexual abuse by Father Moorehouse when he was her teacher. Gráinne’s husband, Donnacha, is the man with whom the narrator had a passionate love affair during their adolescence. Donnacha enforces silence on this issue, so their story remains unspoken and consigned to secrecy. Tóibín’s short story deals with the consequences of an Irish legacy of ignorance and taboos concerning sex. This essay will thus delve into questions regarding Irish culture, the antagonistic but ambiguous connection between the Church and homosexuality, as well as the shame and silence traditionally attached to sex. Tóibín seems to adopt a critical approach to Irish society, complicating public debates surrounding Ireland’s sexual past and the Church scandals. As will be argued, Tóibín does not propose in his story a totalising and explanatory view on the nature of the Irish sexual past, but rather he offers a thorough exploration of its ambiguities and complexities. Keywords: Colm Tóibín; Catholic Church; Irish sexual history; male homosexuality; Church scandals; Ireland